INFLUENCE OF LACTOPROTEINUM SOLUTION WITH SORBITOL ON DNA CONTENT OF CELLS OF ENDOCRINE GLANDS ON THE BACKGROUND OF SKIN BURN IN RATS - Dzevulska І.V.; Kovalchuk О.І.; Cherkasov, E.V.; Majewskyi О.Ye.; Shevchuk, Yu.G.; Pastukhova, V.A.; Kyselova, T.M. (World of Medicine and Biology, 2018)
Damage to the endocrine glands is one of the key pathogenetic factors in skin burns, but intracellular mechanisms of the effect of burn disease and its therapy on these organs continue to be poorly understood. The article presents the results of the study of DNA content in adenohypophysis, adrenal and thymus cells of rats by flowing DNA-cytometry against the background of thermal skin burn and correction of it with solutions of 0.9% NaCl or Lactoproteinum with sorbitol. The study was performed 1, 3, 7, 14, 21 and 30 days after the thermal burn of 2-3 degrees of 21-23% of the body surface and its correction. The statistical processing of the obtained results was carried out in the license package "STATISTICA 6.1" using nonparametric estimation methods. Against the backdrop of applying 0.9% NaCl solution in adenohypophysis cells, occurs a significant decrease in the parameters of the synthetic S-phase (the percentage ratio of the DNA synthesis phase to all cells of the cell cycle) already from 1 day of the experiment, which were restored to the control level only 21 days after the skin burn. The index of the interval SUB-G0G1 (DNA fragmentation index) against the background of applying 0.9% NaCl solution increased significantly from 3 days, and the decrease in the indicator in adenohypophysis cells was observed from the 14th day of the study. In adrenal cells, a significant increase in the S-phase index was observed with a 0.9% NaCl solution correction followed by a decrease from the 3 days of the experiment, and the SUB-G0G1 interval also increased from 1 day, followed by a decrease in this index. Against the background of correction with 0.9% NaCl solution, a significant decrease in the S-phase index of thymus cells was observed 1 day after the skin burn, and on the 3 day there was an increase in this index with its normalization after 14 days from the beginning of the experiment. The parameters of the SUB-G0G1 interval of thymus cells were elevated from 1 day, but after 7 days did not differ from those of the control group. With the use of a solution of Lactoproteinum with sorbitol, the amplitude of the S-phase and the SUB-G0G1 interval of adenohypophysis, adrenal and thymus cells decreased, indicating a cytoprotective effect of this drug. It was concluded that correcting by the 0.9% NaCl solution not sufficiently compensated the DNA damage of the endocrine glands after thermal skin burn, and the use of Lactoproteinum with sorbitol significantly improves the studied DNA content in these organs.